Sistem Penjadwalan Bimbingan Konseling dengan Menerapkan Algoritma Shortest Job First - Fatyana, Nadya; Irawan, Muhammad Dedi; Nasution, Adnan Buyung (TIN: Terapan Informatika Nusantara, 2024)
Counseling guidance is a place for students to consult in overcoming problems and developing the potential of students. In order for counseling guidance to run effectively, scheduling is needed. The preparation of counseling guidance schedules takes a long time so that it causes increasingly long queues. In this study, the method used in research is Research and Development and the system development method uses Rapid Application Development. A website-based scheduling system that uses the Shortest Job First algorithm was developed to shorten long queues. Average waiting time can be reduced by finding the shortest job first, which solves the smallest average waiting time for various operations. By implementing Shortest Job First it can produce a good counseling schedule with a smaller waiting time thus reducing the level of long queues. The accuracy rate of this system is 98.18% accurate.